Fracture risk with intermittent high-dose oral glucocorticoid therapy. - De Vries, F; Bracke, M; Leufkens, H; Lammers, J; Cooper, C; Van Staa, T (2007)
OBJECTIVE: To evaluate the risk of fracture in patients receiving intermittent therapy with high-dose oral glucocorticoids (GCs). METHODS: The study group comprised 191,752 patients from the UK General Practice Database who were 40 years of age and older and received therapy with GCs. The followup time period was divided into the categories of "current" and "no exposure." The daily dose and cumulative dose for each time period were determined. Relative risks were estimated using Cox proportional hazards models, adjusted for age, sex, body mass index, smoking, disease history, and drug history. Fractures of the radius/ulna, humerus, rib, femur/hip, pelvis, or vertebrae were included in the evaluation. RESULTS: Patients who intermittently received high-dose GCs (daily dose > or =15 mg) and had no or little previous exposure to GCs (cumulative exposure < or =1 gm) had a small increased risk of osteoporotic (but not hip/femur) fracture; this risk increased substantially with increasing cumulative exposure. Among patients who received a daily dose > or =30 mg and whose cumulative exposure was >5 gm, the relative risk (RR) of osteoporotic fracture was 3.63 (95% confidence interval [95% CI] 2.54-5.20), the RR of fracture of the hip/femur was 3.13 (95% CI 1.49-6.59), and the RR of vertebral fracture was 14.42 (95% CI 8.29-25.08). CONCLUSION: Intermittent use of high-dose oral GCs (daily dose > or =15 mg and cumulative exposure < or =1 gm) may result in a small increased risk of osteoporotic fracture. Conversely, patients who receive several courses of high-dose GCs (daily dose > or =15 mg and cumulative exposure >1 gm) have a substantially increased risk of fracture.